Use of COVID-19 testing in the first year of the COVID-19 pandemic among cohorts of people at the intersection of drug use and HIV. (1st December 2022) - Gorbach, Pamina M.; Rosen, Alison D.; Moore, Richard; Shoptaw, Steve; Mustanski, Brian; Mehta, Shruti H.; Kirk, Gregory D.; Baum, Marianna K.; Milloy, M.-J.; Hayashi, Kanna; DeBeck, Kora; Kipke, Michele; et al.
Abstract: People living with (PLWH) and at risk for HIV and people who use drugs (PWUD) are at heightened risk for health consequences of COVID-19 because of compromised immunity and high comorbidities. We studied their use of COVID-19 testing during the first year of the COVID-19 pandemic. Eight NIDA funded cohorts across North America in the Collaborating Consortium of Cohorts Producing NIDA Opportunities (C3PNO) administered multiple waves of a COVID-19 survey. Respondents were at least 18 years of age, half PLWH, and many active substance users. Wave one of the COVID-19 survey was May-November, 2020 and wave two October 2020-April 2021. Associations of COVID-19 testing with demographics, socio-demographics, substance use, and HIV-status were assessed. Of the 3762 responses from 2331 individuals, half reported ever COVID-19 testing (49.1 %), with 4.3 % reporting a positive test (163/3762 surveys=4.3 %) and 41.5 % of people reporting current symptoms reported having been tested. In multivariable analysis adjusting for age, sex, and cohort type associations with COVID-19 testing included African American/Black identification compared to Caucasian/white (adjusted odds ratio (AOR)= 0.68; 95 % confidence interval (CI) 0.53, 0.88); being unemployed (AOR=0.61; 95 % CI 0.51, 0.73), and living with HIV (AOR=0.76; 95 % CI0.65, 0.90). Findings from these C3PNO COVID-19 modules suggests that in the first year of the pandemic COVID-19 testing was not broadly accessed by these marginalized populations including PLWH and those unemployed. Factors associated with not testing may also parallel those for vaccination and identify populations needing better access to COVID-19 prevention. Highlights: In the pandemic's first year half in cohorts of people living with HIV (PLWH) and use drugs (PWUD) reported COVID-19 testing. In the pandemic's first year COVID-19 testing was not broadly accessed by marginalized populations i.e. PLWH and unemployed. COVID-19 testing in the pandemic's first year was reported least by PLWH, those unemployed, Black, and reporting drug use. Early in the pandemic only those symptomatic got COVID-19 testing; yet in C3PNO cohorts only a third with symptoms were tested.